Problems and prospects of medical provision for military personnel with COVID-19 in the conditions of medical insurance - V. V. Trokhymchuk; I. O. Pankratov (The State Expert Center of the Ministry of Health of Ukraine, 2023)
To date, the treatment of patients with COVID-19, which caused an unprecedented pandemic in 2019-2023, remains difficult. Military personnel of the Armed Forces of Ukraine during conscription, when returning from business trips and vacations (especially those who are in the incubation period or are asymptomatic) can bring COVID-19 into the unit and cause an outbreak of the disease. The purpose of the work was to conduct an analysis of the existing models of the functioning of insurance medicine in some countries in the world and in Ukraine for their further possible application in the system of medical support of the Armed Forces; factors and conditions affecting the course of the disease on COVID-19 were additionally studied. The main preventive measures against the spread of COVID-19 among military personnel are compliance with sanitary standards, control of disease symptoms and timely vaccination or revaccination. In the treatment of patients with COVID-19, depending on the conditions of stay and the severity of the disease, the following groups of drugs are used: analgesics and antipyretics, rehydration, antiviral, antibacterial and antifungal, low molecular weight heparins, systemic corticosteroids and vitamins, which military personnel receive free of charge. The creation of an effective system of insurance medicine in Ukraine should provide for the possibility for servicemen of the Armed Forces of Ukraine to receive medical care in any health care facility, regardless of departmental subordination, by creating an electronic medical card of a serviceman, which will be included in the electronic health care system of Ukraine. The conducted studies make it possible to draw a conclusion about the need for improvement and further development of the scientific and practical foundations of systematic research in the military medical service of the Armed Forces of Ukraine, improving the quality and efficiency of medical support for servicemen, introducing modern approaches and methods of making sound management decisions on issues of protection and prevention of proliferation COVID-19.